Cesarean delivery rates and indications in pregnancies complicated by diabetes. (30th December 2022) - Olerich, Kelsey L. W.; Souter, Vivienne L.; Fay, Emily E.; Katz, Ronit; Hwang, Joseph K.
Abstract: Objective: Rates of pregestational (PGDM) and gestational diabetes (GDM), and their associated pregnancy complications, are rising. Pregnancies complicated by diabetes have increased cesarean delivery (CD) rates; however, there are limited data regarding the current rates of, and contributing factors to, these deliveries. The Robson Ten Group Classification System (TGCS) is a clinically relevant, standardized framework that can be used to evaluate and analyze cesarean rates. The objective of this study was to evaluate rates of, and indications for, intrapartum, unplanned CD among pregnancies complicated by diabetes, compared to normoglycemic (NG) pregnancies, in a large United States birth cohort. Methods: This retrospective cohort study used chart-abstracted data on births between 24 and 42 weeks' gestation at 17 hospitals that contributed to the Obstetrical Care Outcome Assessment Program database between 01/2016 and 03/2019. The CD rate for NG pregnancies, and pregnancies complicated by gestational and PGDM was calculated and compared using the Robson TGCS. The indications for intrapartum CD in patients with term, singleton, vertex gestations without a prior cesarean were then analyzed. Univariate and multivariate logistic regression models were used to compare the cesarean rate and indications for CD, between the diabetic groups and the NG group. Results were adjusted for maternal age, BMI, neonatal birth weight, and insurance status, as well as clustering by hospital. Results: A total of 86, 381 pregnant people were included in the study cohort. Of these 76, 272 (88.3%) were NG, 8591 (9.9%) had GDM, and 1518 (1.8%) had PGDM. Compared to NG patients, overall cesarean rates were higher in patients with GDM (40.3% vs. 29.7%; aOR 1.25, 95%CI 1.18–1.31) and PGDM (60.0% vs. 29.7%; aOR 2.53, 95%CI 2.04–3.13). This finding remained true when the cohort was restricted to term, singleton, vertex laboring patients without a prior cesarean; compared to NG patients, the cesarean rate was higher in patients with GDM (17.4% vs. 12.2%, aOR 1.37, 95%CI 1.29–1.45) and PGDM (26.0% vs. 12.2%, aOR 2.55, 95%CI 2.00–3.25). The cesarean rate for fetal indications was similar in the GDM (5.7%) and NG (4.4%) groups, while those patients with PGDM had a significantly higher rate (10.4%; aOR 2.01, 95%CI 1.43–2.83). Similarly, the rate of cesarean for labor dystocia in patients with PGDM was significantly higher than in NG patients (16.9% vs. 7.0%, and aOR 2.28, 95%CI 1.66–3.13) while patients with GDM had an intermediate rate (10.6% vs. 7.0%, aOR 1.49, 95%CI 1.40–1.57). Conclusions: The CD rate is significantly higher in pregnancies complicated by diabetes, particularly pregestational, compared to NG pregnancies. Despite controlling for maternal factors and birth weight, pregnancies complicated by diabetes are more likely to undergo an unplanned intrapartum cesarean secondary to labor dystocia than their NG counterparts, but only pregnancies complicated by PGDM have an increased risk of cesarean for fetal indications. More research is needed to understand whether this higher cesarean rate is due to factors intrinsic to diabetes in laboring patients or is due to a difference in the way clinicians manage diabetics in labor.